Global Stability for a Binge Drinking Model with Two Stages - Hai-Feng Huo; Na-Na Song (Discrete Dynamics in Nature and Society)
A more realistic two-stage model for binge drinking problem is introduced, where the youths with alcohol problems are divided into those who admit the problem and those who do not admit it. We also consider the direct transfer from the class of susceptible individuals towards the class of admitting drinkers. Mathematical analyses establish that the global dynamics of the model are determined by the basic reproduction number, R0. The alcohol-free equilibrium is globally asymptotically stable, and the alcohol problems are eliminated from the population if R0<1. A unique alcohol-present equilibrium is globally asymptotically stable if R0>1. Numerical simulations are also conducted in the analytic results.